2015
DOI: 10.1080/00918369.2015.1117898
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Lifetime Suicide Attempts Among Transgender Persons in Argentina

Abstract: This study examined the lifetime prevalence and correlates of attempted suicide among transgender persons in Argentina. Data were derived from a nation-wide, cross-sectional survey conducted in 2013. We assessed individual, social, and structural correlates of reporting a history of attempting suicide using logistic regression. Among 482 participants, the median age was 30, 91% identified as transwomen, and 32% resided in the Buenos Aires metropolitan area. A lifetime suicide attempt was reported by 159 (33%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 39 publications
0
45
0
10
Order By: Relevance
“…Consistent with social desirability bias, asking about suicidality in these environments, especially if not anonymously, may reinforce a transitional narrative where participants feel pressured to give a more positive picture of their mental health for fear of being denied, losing, or being forced to wait longer than necessary for life-saving transition-related services 112,113 Indeed, the practice of delaying transitional treatment due to co-morbid symptomatology like depression and suicidality is widely practiced, 114 though evidence is mounting against the efficacy and ethics of this approach. 78 While set guidelines for transgender suicidality research would help to address this and other concerns, such a tool might not be help to address the expectation of bias created by the optics of the situation (e.g., that patients may not feel comfortable sharing their experiences of suicidality with those responsible for their care, where they are suspected to impact it).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with social desirability bias, asking about suicidality in these environments, especially if not anonymously, may reinforce a transitional narrative where participants feel pressured to give a more positive picture of their mental health for fear of being denied, losing, or being forced to wait longer than necessary for life-saving transition-related services 112,113 Indeed, the practice of delaying transitional treatment due to co-morbid symptomatology like depression and suicidality is widely practiced, 114 though evidence is mounting against the efficacy and ethics of this approach. 78 While set guidelines for transgender suicidality research would help to address this and other concerns, such a tool might not be help to address the expectation of bias created by the optics of the situation (e.g., that patients may not feel comfortable sharing their experiences of suicidality with those responsible for their care, where they are suspected to impact it).…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed description of our sample and recruitment procedures has been described previously. 5,37,38 …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, to be consistent with previous research examining PrEP acceptability among transgender women, 32,44–46 we included a variable addressing lifetime gender-based discrimination in healthcare settings (yes vs. no), assessed with the question: “Due to your transgender identity, have you ever experienced discrimination from physicians, nurses, or other healthcare workers?” as defined in previous studies with this population. 5,37,38 …”
Section: Methodsmentioning
confidence: 99%
“…A score of zero was assigned if the paper contained no information, one if there was a moderate amount, and a score of two indicated that the question was fully addressed (Rushbrooke, Murray & Townsend, 2014). A total of 13 studies achieved a score of 17 or greater, indicating good quality information (Benotsch, Zimmerman, Cathers & McNulty, 2016;Boza & Perry, 2014;de Bolger, Jones, Dunstan & Lykins, 2014;Horvath, Iantaffi, Romine & Bockting, 2014;Kaplan et al, 2015;Keuroghlian, Reisner, White & Weiss, 2015;Marshall et al, 2016;Nuttbrock et al, 2015;Reback, Shoptaw & Downing, 2012;Reisner et al, 2010;Rotondi et al, 2011;Scheim, Bauer & Shokoohi, 2017;Taylor, Bimbi, Joseph, Margolis & Parsons, 2011). A score of between 14 and 16 was given to 6 studies that showed that there were information gaps related to clarity of the aims, data collection methods, research relationships considered and ethics statements (Benotsch, Zimmerman, Cathers & McNulty, 2013;Dadasovich et al, 2017 ;Reisner et al 2010;Reisner, White, Mayer & Mimiaga, 2014;Testa et al, 2012;Wilson, Arayasirikul & Johnson, 2013).…”
Section: Quality Assessmentmentioning
confidence: 99%